2012
DOI: 10.1002/cmdc.201200290
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐ and Voltage‐Gated Potassium (BK) Channel Activators in the 5β‐Cholanic Acid‐3α‐ol Analogue Series with Modifications in the Lateral Chain

Abstract: Large conductance, calcium- and voltage-gated potassium (BK) channels regulate various physiological processes and represent an attractive target for drug discovery. Numerous BK channel activators are available. However, these agents usually interact with the ubiquitously distributed channel-forming subunit and thus cannot selectively target a particular tissue. Here, we performed structure-activity relationship study of lithocholic acid (LCA), a cholane that activates BK channels via the accessory BK β1 subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…1A, bottom structure) as the lead compound. This compound is not a steroid, yet it contains all the structural features previously identified as necessary for cholane steroid activation of BK channels: C3-hydroxyl, hydrophobic nucleus and polar lateral chain (Dopico et al, 2002;Bukiya et al, 2008aBukiya et al, , 2012. The highly hydrophobic methyl 3-hydroxyolean-12-en-30-oate required dissolution in pure DMSO before further dissolution in saline solutions for biologic evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…1A, bottom structure) as the lead compound. This compound is not a steroid, yet it contains all the structural features previously identified as necessary for cholane steroid activation of BK channels: C3-hydroxyl, hydrophobic nucleus and polar lateral chain (Dopico et al, 2002;Bukiya et al, 2008aBukiya et al, , 2012. The highly hydrophobic methyl 3-hydroxyolean-12-en-30-oate required dissolution in pure DMSO before further dissolution in saline solutions for biologic evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…The earliest reported activator, dehydrosoyasaponin-I (DHS-I, the potent compounds extracted from Desmodium adscendens ) activates BK channels only when coexpressed with the β1 subunit in Xenopus oocytes (McManus et al, 1993, 1995), and such β1-dependent activation was also observed in smooth muscle membranes (Bukiya, Patil, Li, Miller, & Dopico, 2012). The xenoestrogen, tamoxifen, and the endogenous steroid hormone 17β-estradiol were also found to activate the BK channel in a β1- dependent manner (De Wet et al, 2006; Dick, Rossow, Smirnov, Horowitz, & Sanders, 2001; Duncan, 2005; Valverde et al, 1999).…”
Section: Modulation Of the Bk Channel's Pharmacological Propertiesmentioning
confidence: 99%
“…A triterpene glycoside was the first and most potent activator to be identified at nanomolecular (100 nM) concentrations, causing an 80 mV lefward shift in V 1/2 and an increase in open probability by means of a direct mechanism (Giangiacomo et al, 1998 ). The identification of this effect in smooth muscle membranes has led to report that such activation depends on the expression of the β1 subunit, although it is unclear whether this effect is determined by other subunits as well (Bukiya et al, 2012 ).…”
Section: The Role Of β Subunits In Bk Channel Pharmacologymentioning
confidence: 99%